SISTEM DIAGNOSIS JERAWAT MENGGUNAKAN METODE FORWARD CHAINING EXPERT SISTEM BERBASIS WEB - Nurani Hidayat; Husni Sulaiman; Andi Nurul Faizah (Journal System Information And Computer, 2024)
The goals of this study are as follows: (1) to learn about the acne diagnosis system using the web-based forward chaining expert system method; (2) Implementing an acne diagnosis system using a web-based, forward-chaining expert system method. This study applies the "forward chaining" method, which is one of the inference methods, starting from known facts and then looking for rules that match existing assumptions or hypotheses to come to conclusions. The system research method uses the waterfall method, which consists of five stages: requirements, design, implementation, verification, and maintenance. From the results of the research that has been done, it can be concluded that the expert system for diagnosing acne uses the "forward chaining" expert method, a web-based system that starts with analyzing system requirements, both hardware and software requirements, and then designs according to needs. This stage also makes rules from the data collected. has been obtained to get the results of the diagnosis and the solution using the forward chaining method. Then implemented into a programming language, Black Box testing and testing with experts are carried out, and the system is hosted and given a domain name so that it can be used.